AB0312 Anti-Cyclic Citrullined Peptide and Ultrasound Activity in Rheumatoid Arthritis. (9th June 2015) - Hamdi, W.; Miladi, S.; Dhahri, R.; Cherif, I.; Zouch, I.; Kaffel, D.; Kchir, M.; Chelli, M.; Ladab, F.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by the presence of rheumatoid factor (RF) and anti-cyclic citrullined peptide (ACPA). ACPA have higher specificity than RF for RA, and are associated with joint radiographic damage and extra-articular manifestations. Objectives: The aim of this study was to evaluate the US RA activity whether the ACPA were present or not. Methods: A cross-sectional study of patients followed-up for RA was conducted. Demographic, clinical and biological data were collected. RF and ACPA mesures were collected from medical records. We calculated the US-DAS28 in order to evaluate accurate activity of RA. All patients had an ultrasound (US) examination of 22 joints of hands (wrists, metacarpophalangeal, proximal interphalangeal). US was performed by an operator blinded to clinical and laboratory data. RA activity was evaluated by US-DAS28 by replacing swollen joints of the hands by joints expressing synovial hypertrophy or hyper vascularization in US. Results: One hundred and eighteen patients were enrolled, 83% were females. The mean age was 53 years-old. The mean duration of the disease was 11.6 months. The RF was positive in 64 (55%) patients and the ACPA was positive in 31 (26%) patients. The median DAS28 was 5, 52 [2, 91-7, 81]. The medianUS-DAS28 was 5.29 [1.98- 7.83]. The comparison between US-DAS28 according to immunological status is showed in table 1 . Conclusions: We conclude that there was no significant difference of RA activity between seropositive or seronegative RA and also whether ACPA was positive or not. The analysis of bone damages should be compared in another study order to determinate the prognostic value of ACPA. References: Jung C, Jisuk B. Relation of rheumatoid factor and anti cyclic citrullined peptide antobody with disease activity in rheumatoid arthritis: cross sectional study. Rheumatol Int 2013. Disclosure of Interest: None declared